Integrative multi-omic analysis reveals potential biomarkers in the cervicovaginal fluid of patients with placenta accrete spectrum - Jiang, Hai; Qu, Jiangxue; Huang, Nana; Li, Zeli; Shi, Xiaoming; Chen, Lian; Zhao, Yangyu (BMC pregnancy and childbirth, 2024)
This study aimed to detect the proteins and metabolites in the cervicovaginal fluid to observe their relationship with the occurrence of placenta accreta spectrum and the potential biomarkers with predictive value. Cervicovaginal fluid samples were collected before delivery from 6 participants of PAS and 6 controls subjects with similar gestational ages. The severity of PAS was evaluated by ultrasound and MRI scoring system and confirmed by the intraoperative findings or pathological examination. We used 4D label-free quantitative proteomics and untargeted metabolomics to identify the proteins and metabolites in cervicovaginal fluid, and analyzed the functions of differential expressed proteins or metabolites in PAS by multi-omics combined with bioinformatics analysis. Proteomics and metabolomics screened 127 and 12 differential expressed proteins and metabolites in CVF of PAS, respectively. Proteins and metabolites that significantly dysregulated in participants with placenta accreta spectrum were factors that regulate angiogenesis, and extracellular matrix proteins that regulate trophoblast invasion. Among them, the important difference expressed proteins/metabolites with representative significance are arginine, GAL7, uPA, MMP9 and ITGAM, that may be useful as potential biomarkers for the prediction and early diagnosis of PAS. Cervicovaginal fluid in patients with PAS presents a protein-metabolic microenvironment that promotes trophoblast invasion, endothelial activation and vascular proliferation.